2022
DOI: 10.15252/emmm.202114844
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 spike spurs intestinal inflammation via VEGF production in enterocytes

Abstract: Severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) can cause gastrointestinal (GI) symptoms that often correlate with the severity of COVID‐19. Here, we explored the pathogenesis underlying the intestinal inflammation in COVID‐19. Plasma VEGF level was particularly elevated in patients with GI symptoms and significantly correlated with intestinal edema and disease progression. Through an animal model mimicking intestinal inflammation upon stimulation with SARS‐CoV‐2 spike protein, we further revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
(57 reference statements)
0
13
0
1
Order By: Relevance
“…It has been shown that SARS‐CoV‐2 spike boosts VEGF levels. High levels of VEGF were observed in previous studies and anti-VEDF therapy proposed to control COVID-19 in critically ill patients ( 36 ), especially those with gastrointestinal symptoms correlated with intestinal edema and disease progression ( 37 ). Conversely, our data have demonstrated that VEGF levels were lower in COVID-19 patients as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been shown that SARS‐CoV‐2 spike boosts VEGF levels. High levels of VEGF were observed in previous studies and anti-VEDF therapy proposed to control COVID-19 in critically ill patients ( 36 ), especially those with gastrointestinal symptoms correlated with intestinal edema and disease progression ( 37 ). Conversely, our data have demonstrated that VEGF levels were lower in COVID-19 patients as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 89%
“…Conversely, our data have demonstrated that VEGF levels were lower in COVID-19 patients as compared to healthy controls. To be noticed, VEGF levels in blood of the animal model is not increased at the initial stages and significantly boosted upon continuous treatment with spike RBD, suggesting that kinetic differences could be observed from a local to systemic spread ( 37 ). Therefore, difference in the early and late timeline kinetics of VEGF should be considered as a plausible explanation for the differences observed between clinical studies.…”
Section: Discussionmentioning
confidence: 97%
“…In patients with gastrointestinal symptoms, there was an increase in VEGF concentration. It was also observed that VEGF was associated with vasodilation and interstitial edema, disease progression even at its early stage in the COVID-19 group with gastrointestinal symptoms ( Zeng et al, 2022 ).…”
Section: Metabolic Changes Induced By Sars-cov-2 In Different Tissuesmentioning
confidence: 96%
“…A study by Zeng et al [2 ▪ ] suggests that patients infected with SARS-CoV-2 with gastrointestinal symptoms have higher circulating and intestinal levels of proinflammatory cytokines, including interleukin (IL)-1α and tumour necrosis factor (TNF)-α, with vascular endothelial growth factor (VEGF) expression also significantly increased in the enterocytes, stimulated by the SARS-CoV-2 spike protein through the Ras-Raf-MEK-ERK pathway (Zeng 2022), functioning to communicate the signal from the surface receptor to the DNA in the nucleus of a cell. The same study demonstrated that blocking ERK/VEGF signalling in vitro and in vivo with ERK inhibitor SCH77298 and VEGF antibody and cancer therapy agent Bevacizumab reduced spike-induced inflammation and hyperpermeability [2 ▪ ]. This finding suggests the potential for cancer patients receiving Bevacizumab to have reduced gastrointestinal inflammation associated with SARS-CoV-2.…”
Section: The Effects Of Cancer Treatments On Angiotensin-converting E...mentioning
confidence: 99%
“…Studies now suggest that SARS-CoV-2 is not limited to the respiratory tract but affects multiple body systems, including the gastrointestinal tract [2 ▪ ]. SARS-CoV-2 infections, and previously SARS-2003 infections, are commonly associated with gastrointestinal symptoms, including diarrhoea, nausea, vomiting, and abdominal pain [3].…”
Section: Introductionmentioning
confidence: 99%